2016
DOI: 10.1186/s12885-016-2217-1
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to compare the detection of HPV-16 biomarkers in salivary oral rinses with tumour p16INK4a expression in head and neck squamous cell carcinoma patients

Abstract: BackgroundHuman papilloma virus-16 (HPV-16) infection is a major risk factor for a subset of head and neck squamous cell carcinoma (HNSCC), in particular oropharyngeal squamous cell carcinoma (OPSCC). Current techniques for assessing the HPV-16 status in HNSCC include the detection of HPV-16 DNA and p16INK4a expression in tumor tissues. When tumors originate from hidden anatomical sites, this method can be challenging. A non-invasive and cost-effective alternative to biopsy is therefore desirable for HPV-16 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 31 publications
5
71
0
6
Order By: Relevance
“…So far, the Aptima HPV assay has been used only to detect HPV mRNA in the saliva of patients with OPC . Another study reported HPV mRNA detection in oral rinses but used homemade, nonstandardized methods and included only patients with HNC …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…So far, the Aptima HPV assay has been used only to detect HPV mRNA in the saliva of patients with OPC . Another study reported HPV mRNA detection in oral rinses but used homemade, nonstandardized methods and included only patients with HNC …”
Section: Discussionsupporting
confidence: 82%
“…In contrast, HPV mRNA detection in oral specimens is very challenging because mRNA is highly susceptible to degradation by the enzymes present in oral fluids. Oral rinses, saliva, and swabs have been used only marginally for HPV mRNA detection in patients with OPC . To the best of our knowledge, no studies have reported HPV mRNA detection in oral rinses of cancer‐free individuals.…”
Section: Introductionmentioning
confidence: 99%
“…HPV-16-driven OPC constitute 90% of HPV-positive OPC [14]. The aetiology and risk factors of oral and oropharyngeal HPV infection remains controversial; however, past studies have shown that these risk factors include oral sex, multiple sexual partners, poor oral hygiene and immunodeficiency conditions [15,16,17,18,19,20]. Identifying key risk factors may help to improve disease screening processes to identify high-risk individuals for developing OPC which may lead to OPC prevention and improve disease mortality [21].…”
Section: Introductionmentioning
confidence: 99%
“…Qureishi et al have reported successful detection of 72.2% HPV genome in their saliva samples obtained from HPV‐HNSCC cases. In a study by Chai et al, E6/E7 primer/probe sets showed 92.9% and 60% sensitivity for HPV‐16 genome in saliva samples for DNA and RNA, respectively. The data presented indicate that our combination of primer/probe sets would improve the sensitivity of detection of HPV16 DNA in tissues and body fluids and improve assessment of disease burden in patients with HPV‐HNSCC.…”
Section: Discussionmentioning
confidence: 99%